Model-based gas leakage detection and isolation in a pressurized system via Laguerre spectrum analysis - Johansson, Andreas; Birk, Wolfgang; Medvedev, Alexander (Proceedings of the 1998 IEEE International Conference on Control Applications (Cat. No.98CH36104), 1998)
This paper deals with gas-leakage detection and isolation in a fine coal injection vessel for a blast furnace process. Functions describing the expected time-domain behaviour of different leakages are developed, thus reducing the leakage isolation problem to pattern recognition. In order to lower the computational burden while preserving the essential dynamic behaviour of a leakage, a truncated Laguerre series representation is used. The Generalized Likelihood Ratio methos is employed to compare the Laguerre of the residual with the Laguerre spectra of the predefined typical leakage functions. Tests of the developed algorithm have been successfully performed at SSAB Tunnplåt, Luleå. Godkänd; 1998; 20061025 (ysko)